Out-of-hospital cardiac arrest following trauma: What does a helicopter emergency medical service offer?. (February 2019) - ter Avest, E.; Griggs, J.; Prentice, C.; Jeyanathan, J.; Lyon, R.M.
Abstract: Introduction: Helicopter emergency medical services (HEMS) are often dispatched to patients in traumatic cardiac arrest (TCA) as they can provide treatments and advanced interventions in the pre-hospital environment that have the potential to contribute to an increased survival. This study, aimed to investigate the added value of HEMS in the treatment of TCA. Methods: We performed a retrospective cohort study of all patients with a pre-hospital TCA who were attended by a non-urban HEMS (Kent, Surrey and Sussex Air Ambulance trust) between July 1st 2013 and May 1st 2018. We investigated how many patients got return of spontaneous circulation (ROSC) at scene, which HEMS specific advanced interventions were performed in these patients, and how these interventions were related to ROSC. Results: During the study period 263 patients with a TCA were attended by HEMS with an average response time of 30 min [range 13–109]. 51 patients (20%) regained ROSC at scene (28 before- and 23 after arrival of HEMS). The HEMS specific interventions of blood product administration (OR 8.54 [2.84–25.72]), and RSI (2.95 [1.32–6.58]) were positively associated with ROSC. Most patients who had a ROSC had one or more HEMS specific interventions being performed – RSI (n = 19, 37%), blood product administration (n = 32, 62%), thoracostomies (n = 36, 71%) and thoracotomy (n = 1, 2%). HEMS also delivered other important interventions to these patients as IV/IO access (n = 20, 39.2%) and endotracheal intubation without drugs (n = 9, 17.6%). Conclusion: HEMS teams should be involved in the treatment of patients with a TCA, even in non-urban areas with prolonged response times, as they provide knowledge and skills that contribute to regaining and maintaining a sustained ROSC in this critically ill and injured cohort of patients.